Effect of mitral regurgitation in stroke risk in patients with nonrheumatic atrial fibrillation. (3rd October 2022) - Dominguez Erquicia, P; Raposeiras-Roubin, S; Abu-Assi, E; Ledo-Pineiro, A; Gonzalez-Garcia, A; Iglesias-Otero, C; Garcia-Campo, E; Iniguez Romo, A
Abstract: Background: Atrial fibrillation (AF) carries a thrombotic risk related to blood stasis produced in left atrium. In patients with rheumatic valve disease and AF, the presence of severe mitral regurgitation (MR) has been shown to reduce the risk of atrial thrombosis and stroke. In patients without rheumatic disease, the results are controversial. Purpose: Our objective is to analyze the association between mitral regurgitation and the incidence of stroke. Methods: We analyzed data from the retrospective registry CardioCHUVI-AF, which includes 15, 720 patients with AF (excluding mechanical prostheses or rheumatic valvular disease) in the Vigo area, from 2014 to 2018. We grouped the patients according to the MR grades: grade 0–2 (15, 194 patients) and grades 3–4 (526 patients). We performed propensity score matching analysis obtaining 2 groups of 511 patients. We analyzed the association between MR and stroke with a competitive risk model, being death the competitive event. Results: During a median follow-up of 4.90 years (IQR 2.85–4.93), 859 (5.5%) patients suffered a stroke. The stroke incidence rate was 1.30 per 100 person-years (95% CI: 1.21–1.39), with no differences between the MR groups. In the univariate analysis, no relationship was observed between the MR grades and stroke (sHR 1.12, 95% CI: 0.79–1.60, P=0.530). After the propensity score matching analysis no significant association was observed between the MR grades and stroke (sHR 0.93, 95% CI: 0.57–1.53, P=0.775) (Figure 1 and 2). This same relationship was evaluated by subgroups of interest: oral anticoagulation, prior heart failure, left ventricular ejection fraction <40%, aortic valve disease, and left atrial dilatation, with results consistent with the overall sample (Figure 2). Conclusions: In our large registry of patients with AF, we did not find a protective effect of significant mitral regurgitation (grades 3–4) on the risk of stroke. Funding Acknowledgement: Type of funding sources: None.